The Effectiveness Of An Individual-Differentiated System Of Health-Improving Exercises In Improving The Health Of Elderly People - Inoyatov Abdullo Shodiyevich (International Journal on Integrated Education, 2026)
The article scientifically substantiates the effectiveness of a system of individual-differentiated health-improving exercises in improving the health of individuals aged 60–74 years. The study was conducted over 24 weeks using a quasi-experimental design (pre-test and post-test). A total of 60 participants were randomly assigned to an experimental group (n=30) and a control group (n=30). In the experimental group, the training load was differentiated within 50–70% of the heart rate, and exercise sessions were organized three times a week for 45–50 minutes. During the research, indicators such as physical performance, arterial blood pressure, heart rate, the 6-minute walk test, hand dynamometry, the sit-to-stand test, the Stange and Genchi tests, and the psycho-emotional state (SAN scale) were studied. The results were analyzed using mathematical and statistical methods (x̄±σ, Student’s t-test), and the level of significance was evaluated according to the criterion p < 0.05. In the experimental group, physical performance increased by 20%, while muscle strength and endurance indicators improved by 18–25%, and respiratory reserve capacity increased by 18–21%. In addition, arterial blood pressure and heart rate normalized. Psycho-emotional stability increased by 28.6%. Compared with the control group, statistically significant positive differences were recorded across all indicators (p < 0.05). The results of the study confirm that a system of individual-differentiated health-improving exercises is an effective means of improving functional, physical, and psycho-emotional indicators in elderly individuals.